Estudo morfológico e molecular de trematódeos transmitidos por Melanoides tuberculata (Mollusca: thiaridae) em coleções aquáticas do Peru - Eduardo Alberto Pulido Murillo (2017)
Melanoides tuberculata (Müller, 1774) is an invasive aquatic snail in South America, where, in recent years, it has been reported as an intermediate host of some species of trematodes. In Peru, despite the occurrence of M. tuberculata be known for several decades, studies on the involvement of this thiarid in the transmission of trematodes are scarce. In the present study, a malacological survey was carried out, in two waterbodies located in the central coast of Peru, between December 2015 and July 2016. It was collected and examined 6,731 specimens of M. tuberculata, of which 127 (1.9%) were found infected with four different cercarian types (Gymnocephalous, Megalurous, Parapleurolophocercous and Pleurolophocercous). Cercariae were used in experimental studies involving, where appropriate, fishes (Poecilia reticulata Peters, 1859) as second intermediate hosts, and chickens (Gallus gallus domesticus Linnaeus, 1758) and rodents (Mus musculus Linnaeus, 1758) as definitive hosts. The developmental stages obtained (cercariae, metacercariae and adults) were used for morphological study by light microscopy. In addition, samples of parasites were subjected to amplification and sequencing of a region of the 18S rRNA gene. The sequences obtained were compared with other from GenBank as well as sequences obtained from Brazilian samples of these trematodes. The morphology of the adult parasites obtained experimentally and the molecular data allowed the identification of Centrocestus formosanus (Nishigori, 1924), Philophthalmus gralli Mathis & Leger, 1910 and Haplorchis pumilio (Looss, 1896), species already reported infecting humans in Asia. Renicola sp. was also identified by morphological traits of cercariae, however molecular sequences did not provide additional taxonomic information. Centrocestus formosanus, H. pumilio and Renicola sp. are reported for the first time in M. tuberculata from Peru, expanding the occurrence area of these species in South America. Moreover, it is confirmed the presence of P. gralli in that country, and the first molecular sequences for South American isolates of the other three species of trematodes were obtained.